Cost-Effectiveness Assessment of Different Glucosamines in Patients with Knee Osteoarthritis: A Simulation Model Adapted to Germany - Bruyère, Olivier; Detilleux, Johann; Reginster, Jean-Yves (Current Aging Science, 2021)
Background: The use of symptomatic slow-acting drugs for osteoarthritis (OA) (e.g., glucosamine, chondroitin) is largely debated in the scientific literature. Indeed, multiple formulations of these agents are available, both as pharmaceutical-grade products and as nutritional supplements , but while all preparations may claim to deliver a therapeutic effect, not all are supported by clinical evidence. Moreover, few data are available regarding the cost-effectiveness of all these formulations. Usually, access to individual patient data is required to perform economic evaluations of treatments, but it can be challenging to obtain. We previously developed a model to simulate individual health utility scores from aggregated data obtained from published OA trials. Objective: In the present study, using our new simulation model, we investigated the costeffectiveness of different glucosamines used in Germany. Methods: We used our validated model to simulate the utility scores of 10 published trials that used different glucosamine preparations. Using the simulated utility scores, the quality-adjusted life years (QALYs) were calculated using the area-under-the-curve method. We used the 2018 public costs of glucosamine products available in Germany to calculate the Incremental Cost/Effectiveness Ratio (ICER). We performed analyses for pharmaceutical-grade Crystalline Glucosamine Sulfate (pCGS) and other formulations of glucosamine (OFG). A cost-effectiveness cut-off of 30,000 /QALY was considered. Results: Of 10 studies in which utility was simulated, four used pCGS, and six used OFG. The ICER analyses showed that pCGS was cost-effective compared to a placebo, with an ICER of 4489 /QALY at month 3, 4112 /QALY at month 6, and 9983 /QALY at year 3. The use of OFG was not cost-effective at any of the time points considered. Conclusion: Using our previously published model to simulate the individual health utility scores of patients, we showed that, in the German context, the use of pCGS could be considered costeffective, while the use of OFG could not. These results highlight the importance of the formulation of glucosamine.
Keywords: Utility score